2013
DOI: 10.1007/s10461-013-0429-9
|View full text |Cite
|
Sign up to set email alerts
|

Adherence Support Approaches in Biomedical HIV Prevention Trials: Experiences, Insights and Future Directions from Four Multisite Prevention Trials

Abstract: Adherence is a critical component of the success of antiretroviral-based pre-exposure prophylaxis (PrEP) in averting new HIV-infections. Ensuring drug availability at the time of potential HIV exposure relies on self-directed product use. A deeper understanding of how to best support sustained PrEP adherence remains critical to current and future PrEP efforts. This paper provides a succinct synthesis of the adherence support experiences from four pivotal PrEP trials—Centre for the AIDS Programme of Research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
103
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 23 publications
1
103
0
Order By: Relevance
“…7,23,38 An evaluation of interventions to promote adherence to PrEP recommended participant-centered approaches, including addressing the specific context in which an individual incorporates and negotiates PrEP use. 41 While complex, resource-intensive interventions are most effective for improving adherence to medical interventions in general, a systematic review also found evidence to support low-cost, low-intensity interventions that provided education or telephone calls. 38 CDC guidelines recommend that clinicians incorporate motivational interviewing into their visits for prescribing PrEP with 4 simple items: (1) When you have taken medications previously?…”
Section: Supporting Adherence To Prepmentioning
confidence: 99%
“…7,23,38 An evaluation of interventions to promote adherence to PrEP recommended participant-centered approaches, including addressing the specific context in which an individual incorporates and negotiates PrEP use. 41 While complex, resource-intensive interventions are most effective for improving adherence to medical interventions in general, a systematic review also found evidence to support low-cost, low-intensity interventions that provided education or telephone calls. 38 CDC guidelines recommend that clinicians incorporate motivational interviewing into their visits for prescribing PrEP with 4 simple items: (1) When you have taken medications previously?…”
Section: Supporting Adherence To Prepmentioning
confidence: 99%
“…Adherence to frequent dosing is burdensome to the user and has emerged as a key factor in explaining the heterogeneous efficacy outcomes of HIV-1 preexposure prophylaxis (PrEP) clinical trials (4)(5)(6)(7). It is well established across different delivery methods that adherence to therapy is inversely related with the dosing period (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Multiple HIV PrEP clinical trials have demonstrated that vaginal and oral ARV regimens based on the nucleoside reverse transcriptase inhibitor (NRTI) tenofovir (TFV) can be effective in susceptible men, women, and partners of HIV-infected individuals (3)(4)(5)(6)(7)(8)(9), but other studies based on analogous drug regimens were unsuccessful at reducing the rates of HIV acquisition (10)(11)(12). A critical factor driving success in these trials appears to involve sustaining high adherence to frequent dosing (13).…”
mentioning
confidence: 99%